2005
DOI: 10.1200/jco.2005.08.375
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral and Immunologic Response After Vaccination of Melanoma Patients With an ALVAC Virus Encoding MAGE Antigens Recognized by T Cells

Abstract: Repeated vaccination with ALVAC miniMAGE-1/3 is associated with tumor regression and with a detectable CTL response in a minority of melanoma patients. There is a significant correlation between tumor regression and CTL response. The contribution of vaccine-induced CTL in the tumor regression process is discussed in view of the immunologic events that could be analyzed in detail in one patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(106 citation statements)
references
References 34 publications
1
104
0
1
Order By: Relevance
“…49 , 50 Moreover, treatment-driven TCR repertoire diversity has been related to different treatment vaccine formulations. 51 , 52 In melanoma, a highly restricted TCR repertoire has been linked to metastasis regression during cytokine therapy. 53 Neo-adjuvant Sipuleucel-T treatment of prostate cancer subjects has been shown to induce a narrowed TCR diversity in the periphery but enlarged in the tumor, with these differences reduced during the treatment, suggesting that vaccine-driven T cells were infiltrating the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…49 , 50 Moreover, treatment-driven TCR repertoire diversity has been related to different treatment vaccine formulations. 51 , 52 In melanoma, a highly restricted TCR repertoire has been linked to metastasis regression during cytokine therapy. 53 Neo-adjuvant Sipuleucel-T treatment of prostate cancer subjects has been shown to induce a narrowed TCR diversity in the periphery but enlarged in the tumor, with these differences reduced during the treatment, suggesting that vaccine-driven T cells were infiltrating the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that vaccination with MAGE has effect on metastases (Thurner et al, 1999;Marchand et al, 2003;Kruit et al, 2005;Lurquin et al, 2005;Van Baren et al, 2005), but improvement of MAGE vaccines is strongly needed. In previous studies, we have shown that immunisation with Mage-b combined with GM-CSF plasmid DNA and thioglycollate reduced the number of metastases by 65% compared with the control group in a highly metastatic breast tumour model, 4T1 (Gravekamp et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The MAGE antigens are particularly interesting for the development of breast cancer vaccines, because their expression (MAGE-A and/or MAGE-B) has been frequently detected in human breast tumour biopsies (92%) (Park et al, 2002), but not in normal tissues (De Backer et al, 1995;De Plaen et al, 1999). Various clinical trials have shown that vaccination with MAGE-1 and -3 peptides or protein, in patients with melanoma was effective against metastases (Thurner et al, 1999;Marchand et al, 2003;Kruit et al, 2005;Lurquin et al, 2005;Van Baren et al, 2005). These human clinical trials not only show the potential of MAGE vaccination against metastases but also the need to further optimise the efficacy of MAGE-based vaccines to improve the clinical outcome.…”
mentioning
confidence: 99%
“…Because of their restricted expression to germ cells and malignant tissues, there should be no deletion of a high-affinity T cell repertoire and theoretically a low risk of preexisting immune tolerance. Thus, the testis-restricted CT Ags are being used as targets in several vaccination trials (23). In particular, NY-ESO-1 and CT Ags belonging to the MAGE and GAGE families have been shown to elicit spontaneous cellular and/or humoral immune responses in cancer patients (24 -28).…”
Section: Ultiple Myeloma (Mm) 3 Is a B Cell Neoplasia Charac-mentioning
confidence: 99%